Acute effects of endurance exercise on jumping and kicking performance in top-class young soccer players - Juarez, D.; Lopez de Subijana, C.; Mallo, J.; Navarro, E. (European Journal of Sport Science, 2011)
The aim of this study was to examine the acute effects of endurance exercise on jumping and kicking performance in young soccer players. Twenty-one top-class young soccer players (16.1±0.2 years) performed a countermovement jump test and a maximal instep soccer kick test before and after running for 20 min on a treadmill at 80% of their individual maximum heart rate. Two force platforms were used to obtain the following parameters during the countermovement jump: jump height, maximum power, maximum power relative to body mass, maximum vertical ground reaction force, maximum vertical ground reaction force relative to body mass, and maximum vertical ground reaction force applied to each leg. Maximum vertical ground reaction force and maximum vertical ground reaction force relative to body mass applied to the support leg during the kicks were also calculated with a force platform. The kicking motion was recorded using a three-dimensional motion-capture system. Maximum velocity of the ball, maximum linear velocity of the toe, ankle, knee and hip, and linear velocity of the toe at ball contact during the kicks were calculated. Non-significant differences were found in the parameters measured during the countermovement jump and the maximal instep soccer kick test before and after running, suggesting that the jumping and kicking performances of top-class young soccer players were not significantly affected after 20 min treadmill running at 80% of their individual maximum heart rate.